An Evaluation of a Parent Group for Survivors of Intimate Partner Violence - Renner, Lynette M. (Journal of family violence, 2022)
Researchers continue to demonstrate the significant physical and mental health consequences to women who experience intimate partner violence (IPV) and children exposed to IPV. However, more research is needed to examine group interventions that support mothers, their children, and the parent-child relationship in the aftermath of IPV. We analyzed data provided by women who participated in a 12-week parent group. The objectives of the parent group were for mothers to better understand their children’s developmental experience of IPV and to break the secret of domestic violence in their family. The sample included 15 women who completed the group and the baseline, midpoint, and endpoint surveys. Eleven of these women also completed a semi-structured interview three months following the group. Survey items and interview topics focused on group process and outcomes. Women reported the group helped them feel less alone in their experience of IPV and they valued having a space to learn and discuss new concepts that related to their experiences and their children’s experiences of IPV. They reported more confidence in identifying their child’s feelings and being a safe person to whom their children could express their anger. Women also reported they developed greater coping and communication tools, and a strengthened mother-child bond, through group participation. Group interventions are an important format for learning and sharing for some mothers who have experienced IPV, though more evaluation is needed on what components of these group interventions are the most supportive of mothers’ healing and growth.